Consumer Protection in the Health Sector: The Legal Responsibilities of Pharmacists - Setiawan, Sartono; Hardyansah, Rommy; Khayru, Rafadi Khan; Putra, Arif Rachman; Suwito (Journal of Social Science Studies, 2023)
This study aims to analyse the legal protection of patients in cases of pharmacist negligence in Indonesia, focusing on civil, criminal and administrative liability. Pharmacists have a strategic role in healthcare, but their negligence can have a serious impact on patient safety. Civil law protection allows patients to sue for damages under Article 1365 of the Civil Code, while criminal protection serves to provide a deterrent effect through the application of sanctions on negligence that causes serious injury or death. On the other hand, administrative law through regulations such as Permenkes No. 74/2016 provides supervision of pharmaceutical practices with sanctions ranging from reprimands to revocation of practice licences. This study found that although the regulatory framework is in place, its implementation still faces obstacles such as lack of supervision, low legal awareness of pharmacists, and barriers to legal access for patients. Using a normative juridical approach, this study recommends increased supervision, legal education, and ease of legal access to improve the effectiveness of patient protection.